Reflecting on Student Radio Work: Stories from the Studios - Mollgaard, Matt; Neill, Karen (Informa UK Limited)
This article sets out to illuminate an often-overlooked aspect of radio broadcasting, the experiences of its workers. It uses the reflections of workers from student radio in New Zealand to discuss the profound impact working in this sector has had on the lives of these people. We do this by conducting a thematic analysis of online survey feedback in order to understand how student radio work shaped the lives of the respondents. This article is designed to center the place of workers and their experiences in media organizations and of media work. The article interrogates the life-long impacts of working in student radio in terms of workers’ careers, wellbeing and sense of belonging to a unique community. It does this by drawing thematic conclusions about student radio as a space for developing purpose, identity and belonging, a catalyst for the independent music scene and a breeding ground for creativity and media careers. This led to a lifelong passion for student radio and a lasting legacy for student radio workers.
Keywords: 1902 Film, Television and Digital Media; 1903 Journalism and Professional Writing; 3605 Screen and digital media; 4701 Communication and media studies